Barriers to primary care clinician adherence to clinical guidelines for the management of low back pain: Protocol of a systematic review and meta-synthesis of qualitative studies - Slade, S.; Kent, Peter; Bucknall, T.; Molloy, E.; Patel, S.; Buchbinder, R. (BM J Group, 2015)
Introduction: Low back pain is the highest ranked condition contributing to years lived with disability, and is a significant economic and societal burden. Evidence-based clinical practice guidelines are designe d to improve quality of care and reduce practice variation by providing graded recommendations based on the best available evidence. Studies of low back pain guideline implementation have shown no or modest effects at changing clinical practice. Objectives: To identify enablers and barriers to adherence to clinical practice guidelines for the management of low back pain. Methods and analysis: A systematic review and meta-synthesis of qualitative studies that will be conducted and reported using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement guidelines. Eight databases will be searched using a priori inclusion/exclusion criteria. Two independent reviewers will conduct a structured review and meta-synthesis, and a third reviewer will arbitrate where there is disagreement. This protocol has been registered on PROSPERO 2014. Ethics and dissemination: Ethical approval is not required. The systematic review will be published in a peer-reviewed journal. The review will also be disseminated electronically, in print and at conferences. Updates of the review will be conducted to inform and guide healthcare translation into practice. Trial registration number: PROSPERO 2014: CRD42014012961. Available from http://www.crd.york.ac.uk/PROSPERO/display-record.asp?ID=CRD42014012961 http://www.crd.york.ac.uk/PROSPERO/display-record.asp?ID=CRD42014012961